Cover Image. (6th April 2022) - Miripour, Zohreh Sadat; Abbasvandi, Fereshteh; Aghaee, Parisa; Shojaeian, Fatemeh; Faramarzpour, Mahsa; Mohaghegh, Pooneh; Hoseinpour, Parisa; Namdar, Naser; Hassanpour Amiri, Morteza; Ghafari, Hadi; Parniani, Mohammad; Kaviani, Ahmad; et al.
Abstract : The cover image is based on the Research Article Human study on cancer diagnostic probe (CDP) for real‐time excising of breast positive cavity side margins based on tracing hypoxia glycolysis; checking diagnostic accuracy in non‐neoadjuvant cases by Mohammad Abdolahad et al., https://doi.org/10.1002/cam4.4503 .